Techno-economic and environmental aspects of the production of medium scale ligno-cellulosic ethanol under Egyptian conditions - Shadia R. Tewfik; Abdel Ghani M.G. Abulnour; Mohamed H. Sorour (Egyptian Journal of Petroleum)
As a result of actual pilot experimental data and guided by international and national reported estimates, this techno-economic study on a 20,000 ton/y ethanol production plant from rice straw has been conducted. The process essentially comprises preparation of the raw materials, alkaline pretreatment, simultaneous saccharification and fermentation (SSF) and dehydration. For the proposed capacity, costs have been estimated based on published information for the equipment as updated to 2013. Operating costs have been estimated according to experimental results of the research team and published information. Financial and sensitivity analyses have been conducted for optimistic and pessimistic scenarios for investment and operating costs and varying sales price of ethanol in the range $0.76/kg–$0.84/kg. Results indicate that positive present values have been obtained at the prevailing discount rate of 3%. The Internal Rate of Return (IRR) exceeds the discount rate considerably for the optimistic assumptions and is rather marginal for the pessimistic scenarios. In general, the process is considered technically and economically viable.